2020
DOI: 10.1038/s41598-020-67257-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunity of nanoscale magnetic tunnel junctions with perpendicular magnetic anisotropy to ionizing radiation

Abstract: Spin transfer torque magnetic random access memory (Stt-MRAM) is a promising candidate for next generation memory as it is non-volatile, fast, and has unlimited endurance. Another important aspect of Stt-MRAM is that its core component, the nanoscale magnetic tunneling junction (MtJ), is thought to be radiation hard, making it attractive for space and nuclear technology applications. However, studies on the effects of ionizing radiation on the STT-MRAM writing process are lacking for MTJs with perpendicular ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 54 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…al. [96] demonstrated that MTJs are even resilient to radiation that is 100× greater than what is observed on particularly harsh inter-planetary travel [11,156]. Therefore, MTJs represent leading candidates for space applications [39,67].…”
Section: Radiationmentioning
confidence: 99%
See 1 more Smart Citation
“…al. [96] demonstrated that MTJs are even resilient to radiation that is 100× greater than what is observed on particularly harsh inter-planetary travel [11,156]. Therefore, MTJs represent leading candidates for space applications [39,67].…”
Section: Radiationmentioning
confidence: 99%
“…Without the earth's atmosphere to shield radiation from space, satellites are exposed to much higher levels of radiation. Non-volatile memory is at an advantage in this domain, as the memory devices it uses are highly resistant to radiation [96]. However, non-volatile memory still relies on CMOS circuitry for memory access and external control, which also applies to non-volatile PIM.…”
Section: Introductionmentioning
confidence: 99%
“…Both studies concluded that ionizing radiation has a negligible impact either on TMR or on field-induced switching properties of i-MTJs. Recently, Montoya et al 14 characterized the current-induced switching property of nanoscale MTJs with perpendicular magnetic anisotropy (p-MTJs) before and after gamma radiation, which also demonstrated that all key properties of p-MTJs are robust against ionizing radiation of cobalt-60 gamma-ray. It has been pointed out that gamma-ray radiation is involved more in electron-hole pair creation rather than in trap generation.…”
Section: High-dose X-ray Radiation Induced Mgo Degradation and Breakd...mentioning
confidence: 99%
“…Fanghui Ren et al [10] demonstrated that the electrical and the magnetic properties of MgO-based MTJs were not affected by gamma radiation and epithermal neutrons. Eric Arturo Montoya et al [11] proved that the critical properties of nanoscale perpendicular magnetic anisotropy in STT-MTJs, such as magnetoresistance, magnetic field switching, and current-induced switching, are robust against ionizing radiation.…”
Section: Introductionmentioning
confidence: 99%